Ciborgues Coquetes: a condição da mulher no Século XXI pela cultura Ciberfeminina - Ferraz, Cláudia Pereira (2015)
This dissertation is an ethnographic methodological study on feminine and feminist communities of Facebook based on recent studies for data collection and analysis at the virtual context. From the phenomenon of the explosion of technology in social media, I mapped a female category in the social network, that I have termed as "Ciberfeminine . Such terminology, this is a representation of the patriarchal and media features in the femininity digital culture. This analyse used like resource, those online personal profiles (among girls, women and ladies) used to circumvent the ciberfeminino was done, from the practice of hidden observation of personal pages and monitoring of selected communities. The reflex of female at the social network is analysed in this dissertation, from the portraits and self-portraits are "posted", which reproduce a virtual actresses acting in Ciberfeminine at the social network, as Cyborgs Coquettish . Like this, I showed the similarities of the profile characteristics of female culture presented, immersed in Simmelian reference, where the explicit sensuality in the poses, in the looks and in the smiles, surround a segment of female culture called "coquetry." They use the instrumentalized technology to reproduce and disseminate the female image based on sexualized "beauty", working in this way, the social / virtual self-marketing. On the other hand, in the same sphere of social / virtual relationships, the traditional condition persists massacring the woman's sexuality release. As a counterpoint, I presented the recent developments of causes, on which feminists communities in Facebook have raised and have challenged. In this context, the work approaches the female class split into social niches, propagators of coercive values, scaling for online life the ideal of Foulcault panopticon. Thus, I demonstrated that social pressures for visibility may stigmatize or disciplinary female categories, from aesthetic values of image and/or from traditional moral to feminine principles, reflecting the maximum of quantitative signs in Brazilian feminine exposed on Facebook